Molecular biology of the gene - Watson, James D; Watson, James D (New Delhi: Affilited East-West Press Limited, 2024)
The classic book from Dr James Watson, nobel laureate , on the 71st anniversary of the discovery of the structure of the DNA in 1953. The field of molecular biology as we understand today was born out of the discovery of the DNA Strucure.
Introductory course on molecular biology
Keywords: Botany -- Molecular biology -- Gene